Mass Customized Outlook for Regenerative Heart Failure Care - Satsuki Yamada (MDPI AG, 2021)
Heart failure pathobiology is permissive to reparative intent. Regenerative therapies exemplify an emerging disruptive innovation aimed at achieving structural and functional organ restitution. However, mixed outcomes, complexity in use, and unsustainable cost have curtailed broader adoption, mandating the development of novel cardio-regenerative approaches. Lineage guidance offers a standardized path to customize stem cell fitness for therapy. A case in point is the molecular induction of the cardiopoiesis program in adult stem cells to yield cardiopoietic cell derivatives designed for heart failure treatment. Tested in early and advanced clinical trials in patients with ischemic heart failure, clinical grade cardiopoietic cells were safe and revealed therapeutic improvement within a window of treatment intensity and pre-treatment disease severity. With the prospect of mass customization, cardiopoietic guidance has been streamlined from the demanding, recombinant protein cocktail-based to a protein-free, messenger RNA-based single gene protocol to engineer affordable cardiac repair competent cells. Clinical trial biobanked stem cells enabled a systems biology deconvolution of the cardiopoietic cell secretome linked to therapeutic benefit, exposing a paracrine mode of action. Collectively, this new knowledge informs next generation regenerative therapeutics manufactured as engineered cellular or secretome mimicking cell-free platforms. Launching biotherapeutics tailored for optimal outcome and offered at mass production cost would contribute to advancing equitable regenerative care that addresses population health needs.